Community Nursing Services in England An Historical Policy Analysis - Bramwell, Donna; Checkland, Kath; Shields, Jolanta; Allen, Pauline (Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This open access book provides an historical account of the ways in which community nursing services in England have been shaped by policy changes, from the inception of the NHS in 1948 to the present day. Focusing on policies regarding the organisation and provision of community nursing services, it offers an important assessment of how community nursing has evolved under successive governments. The book also provides reflections on how historic policies have influenced the service of today, and how lessons learnt from the past can inform organisation and delivery of current and future community nursing services. It is an important resource for those researching community nursing and health services, as well as practitioners and policy makers. Donna Bramwell is Research Associate at the University of Manchester, UK. Her research interests include the sociology of health and illness, primary care health policy, and health organisations. Kath Checkland is Professor of Health Policy and Primary Care at the University of Manchester, UK. Her research addresses all aspects of system organisation and management, with a particular focus on commissioning and primary care. Jolanta Shields is Lecturer in Politics at Leeds Beckett University, UK. Her research explores the politics of health inequalities and how health system governance is shaped by wider socio-political forces. Pauline Allen is Professor of Health Systems Organisation at London School of Hygiene and Tropical Medicine, UK. Her research examines the organisation of the health systems, with a particular focus upon governance, accountability and contractual approaches to system management.